Service-based network selection in C-ITS vehicular networks. (25th January 2021) - Teixeira, Lincoln Herbert; Huszák, Árpád
Cooperative intelligent transport systems (C-ITS) are made up of vehicular applications and provide a framework for road users and traffic managers to share information between stakeholders. Different access technologies exist that can support V2X communication, however, each one has its own advantage and drawback and cannot be used effectively for all types of services. The alternative to avoid this issue is to employ multiple networks and select the best one available, by using an intelligent network selection algorithm. It is also possible to use extra information, like position and navigation route information, to predict the distances between the hosts to improve the user experience. This work presents the SISS algorithm and compares its performance with the widely used TOPSIS algorithm to decide which network option is the best for each application, taking the service requirements into account.